Urbanization may enhance tornado potential: A single case report - Fan, Jiwen; Wang, Jingyu; Lin, Yun (Frontiers in Earth Science, 2023)
Tornadoes pose a risk of catastrophic economic loss and casualty in the United States. Modification of land use by urbanization alters the meteorological conditions that may impact tornado formation and intensification processes. Here we explored the simulated impact of Kansas City urbanization on the tornado potential of a supercell storm. In this studied case, we found that urbanization might enhance tornado potential by (a) strengthening the low-level streamwise vorticity in the storm inflow region, thus forming stronger rotating updrafts; and (b) intensifying near-surface horizontal vorticity near the boundary of the forward-flank cold pool which increases the ingestion, tilting, and stretching of streamwise horizontal vorticity into vertical vorticity. The former results from the stronger east-to-west pressure perturbation gradient due to the faster, stronger outflow boundary, and the latter is mainly a result of the larger temperature contrast as a result of stronger cold pools and inflow oriented perpendicular to the temperature gradient. We emphasize that our conclusions only represent one possibility of how urbanization would affect tornado potential, and more systematic examination is needed to achieve a more general conclusion.